Preparative Separation and Purification of Flavonoids from Ephedra sinica Stapf. by High-Speed Counter-Current Chromatography - Fang, Lei; Geng, Wenmao; Zhou, Jie; Cao, Ruimin; Wang, Zhiwei; Li, Jialian; Geng, Yanling (Asian Journal of Chemistry, 2015)
Preparative high-speed counter-current chromatography was successfully performed for separation and purification of flavonoids from the stem of Ephedra sinica Stapf. with a two-phase solvent system composed of petroleum ether-ethyl acetate-methanol-water (0.5:3.5:1:3, v/v/v/v). This separation process produced four flavonoids, mahuannin A (1), mahuannin D (2), dihydroquercetin (3) and catechin (4) from 350 mg of crude sample in a one-step separation with purities of 98.8, 98.6, 98.3 and 98.2 %, respectively. The structures of these flavonoids were confirmed by ESI-MS, 1H NMR and 13C NMR.